Construction of a new lipase- and xylanase-producing oleaginous yeast consortium capable of reactive azo dye degradation and detoxification. (October 2020) - Ali, Sameh Samir; Al-Tohamy, Rania; Xie, Rongrong; El-Sheekh, Mostafa M.; Sun, Jianzhong
Graphical abstract: Highlights: A novel multipurpose oleaginous yeast consortium constructed for multi-bioprocess purposes. Its maximum intracellular and extracellular lipase activity is 7.34 and 8.15 U/mg, respectively. It showed potential to produce cellulases, hemicellulases and to accumulate triacylglycerol. It showed significant decolorization performance on reactive azo dyes (single and a mixture). Phytotoxicity test confirm that the biodegraded products of tested reactive dye are non-toxic. Abstract: A new oleaginous yeast consortium Y-BC-SH which stands for molecularly identified species Yarrowia sp., Barnettozyma californica and Sterigmatomyces halophilus was successfully constructed in this study. This multipurpose oleaginous yeast consortium was developed based on its higher ability to accumulate large amounts of lipids in the form of triacylglycerol, grow on xylose, produce lipase and xylanase and it could rapidly decolorize and degrade commonly-used textile reactive azo dyes. The specific enzyme activities of lipase, xylanase, xylan esterase, β-xylosidase, CMCase, β-glucosidase and cellobiohydrolase produced by Y-BC-SH were significantly higher than that of individual strains. As chemical oxygen demand reduction had occurred in the dye mixture solutions, it was evidence of their color removal and mineralization by Y-BC-SH. The significant induction of oxidoreductive enzymes by Y-BC-SH was probably due to the coordinated metabolic interactions of the individual strains. Phytotoxicity assay confirmed that metabolites generated after dye degradation by Y-BC-SH are non-toxic.